Telaah Kritis Terhadap Dekonstruksi Bahasa Gender Dalam Pengajian Islam - Shalahuddin, Henri; Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2013)
This paper will examine the deconstruction of language of gender in Islamic studies as widely promoted by feminist scholars in Indonesia. The feminist scholars perceive the language of gender as a method to legalize discrimination against women as well as to strengthen the hierarchical gender relations. The deconstruction of the language of gender has been initiated by the feminist scholars to ‘challenge’ the domination of patriarchal culture and to build a so called ‘balanced understanding’ of Islamic studies in favor of women. In fact, on the other hand, this method generates contemporary insights and interpretation of Islamic studies which apparently contradict the basic principles of Islamic teaching and the essence of terminologies in Quranic text in particular as promoted by most trusted and competent Muslim scholars. This study was conducted to contend the above mentioned feminist scholars argument and prove that the argument of feminist scholars who view that the biased gender in Islamic teaching was the result of the application of Arabic language is a pointless and totally flawed argument. For this purpose, the writer carefully exercises analytical method on the content of books, journals, and papers of feminist scholars in this study.